Patient confidence regarding secondary lifestyle modification and knowledge of 'heart attack' symptoms following percutaneous revascularisation in Japan: a cross-sectional study. Issue 3 (16th March 2018) - Kitakata, Hiroki; Kohno, Takashi; Kohsaka, Shun; Fujino, Junko; Nakano, Naomi; Fukuoka, Ryoma; Yuasa, Shinsuke; Maekawa, Yuichiro; Fukuda, Keiichi
Abstract : Objective: To assess patient perspectives on secondary lifestyle modification and knowledge of 'heart attack' after percutaneous coronary intervention (PCI) for coronary artery disease (CAD). Design: Observational cross-sectional study. Setting: A single university-based hospital centre in Japan. Participants: In total, 236 consecutive patients with CAD who underwent PCI completed a questionnaire (age, 67.4±10.1 years; women, 14.8%; elective PCI, 75.4%). The survey questionnaire included questions related to confidence levels about (1) lifestyle modification at the time of discharge and (2) appropriate recognition of heart attack symptoms and reactions to these symptoms on a four-point Likert scale (1=not confident to 4=completely confident). Primary outcome measure: The primary outcome assessed was the patients' confidence level regarding lifestyle modification and the recognition of heart attack symptoms. Results: Overall, patients had a high level of confidence (confident or completely confident, >75%) about smoking cessation, alcohol restriction and medication adherence. However, they had a relatively low level of confidence (<50%) about the maintenance of blood pressure control, healthy diet, body weight and routine exercise (≥3 times/week). After adjustment, male sex (OR 3.61, 95% CI 1.11 to 11.8) and lower educational level (OR 3.25; 95% CI 1.70 to 6.23) were identified as factors associated with lower confidence levels. In terms of confidence in the recognition of heart attack, almost all respondents answered 'yes' to the item 'I should go to the hospital as soon as possible when I have a heart attack'; however, only 28% of the responders were confident in their ability to distinguish between heart attack symptoms and other conditions. Conclusions: There were substantial disparities in the confidence levels associated with lifestyle modification and recognition/response to heart attack. These gaps need to be studied further and disseminated to improve cardiovascular care.